Preliminary study of renewable Pico-Mini hydro electrification in Royal Belum, Perak - Mohd. Nor, M.F. (Asian Research Publishing Network, 2016)
PV/Diesel Power Generation Scheme was adopted to replace the stand-alone diesel power generation system in rural villages and schools in Malaysia. As the diesel fuel costs fluctuates over the year and the PV module showing inefficiency and incapability to totally replace diesel generators, hydro power is identified as an essential add-on power sources to the current PV/Diesel system. Hence, this paper studies the preliminary elements and analyse the potential for PV/Diesel/Pico Hydro hybrid system to be applied in SK Sungai Tiang in Royal Belum, Perak. The comparison between PV/Diesel hybrid and PV/Diesel/Pico Hydro hybrid with emphasis placed on the amount of fuel savings and total cost needed to implement the PV/Diesel/Pico Hydro hybrid based on capital cost and operational & maintenance cost (O&M). Â© 2006-2016 Asian Research Publishing Network (ARPN).